2000
DOI: 10.1074/jbc.275.11.8143
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of the PEST-like Endocytosis Signal of the Yeast a-Factor Receptor

Abstract: A 58-residue-long, PEST-like sequence within the yeast a-factor receptor (Ste3p) specifies the ubiquitination, endocytosis, and consequent vacuolar degradation of the receptor protein (Roth, A. F., Sullivan, D. M., and Davis, N. G. (1998) J. Cell Biol. 142, 949 -961). The present work investigates three lysyl residues that map within this sequence as the potential ubiquitin acceptor sites. Lys 3 Arg substitution mutants were tested for effects on both ubiquitination and endocytosis. Results indicate that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 40 publications
4
110
1
Order By: Relevance
“…Lys-48-linked ubiquitin tagging is mostly used to target proteins for degradation by the proteasome, whereas Lys-63-linked ubiquitination has been linked to numerous cellular events that do not rely on the degradative signaling via the proteasome. Of these, the endocytosis of membrane proteins (41)(42)(43)(44), protein sorting and trafficking (45)(46)(47), and post-replicative DNA repair (48) are well characterized. Doss-Pepe et al (49) have reported recently that Parkin has dual specificity for the assembly of ubiquitin chains through two different linkages to the substrate (Ub-Lys-48 and Ub-Lys-63).…”
Section: Discussionmentioning
confidence: 99%
“…Lys-48-linked ubiquitin tagging is mostly used to target proteins for degradation by the proteasome, whereas Lys-63-linked ubiquitination has been linked to numerous cellular events that do not rely on the degradative signaling via the proteasome. Of these, the endocytosis of membrane proteins (41)(42)(43)(44), protein sorting and trafficking (45)(46)(47), and post-replicative DNA repair (48) are well characterized. Doss-Pepe et al (49) have reported recently that Parkin has dual specificity for the assembly of ubiquitin chains through two different linkages to the substrate (Ub-Lys-48 and Ub-Lys-63).…”
Section: Discussionmentioning
confidence: 99%
“…The acronym PEST refers to an enrichment of proline (P), aspartate and glutamate (E), serine (S), and threonine (T) residues (Rogers et al 1986). In many cases, PEST sequences are targets for phosphorylation and implicated in the regulation of protein turnover (Rechsteiner and Rogers 1996;Marchal et al 1998;Roth and Davis 2000). Both PEST-1 (amino acid residues 544-560) and PEST-2 (residues 843-893) of FRQ appear to be phosphorylated in vivo Schafmeier et al 2006).…”
Section: Physical Properties Of Frqmentioning
confidence: 99%
“…Because recombinant Ub proteins that have NH 2 -terminal epitope extensions, such as His 6 -Ub, myc-Ub, and glutathione S-transferase-Ub, can substitute for wild-type Ub in a variety of Ub conjugation reactions (24 -28), there is a largely untested assumption that wild-type Ub situated at the COOH terminus will trigger the ubiquitin fusion degradation pathway, resulting in degradation of X-Ub fusions by proteasome. This issue is complicated by the conjugation of the X-Ub to target proteins via Ub Gly 76 , which is available for isopeptide bond formation (22).…”
Section: Ubiquitin (Ub)mentioning
confidence: 99%